1-[(Z)-(5-Methyl-2-pyridyl)iminiomethyl]-2-naphtholate - Liu, Xin-Yu (International Union of Crystallography, 2010)
In the zwitterionic title compound, C(17)H(14)N(2)O, the dihedral angle between the naphthalene and pyridine ring systems is 3.56 (9)° and an intramolecular N—H⋯O hydrogen bond generates an S(6) ring. In the crystal, molecules are linked by C—H⋯O interactions.